Significance of and exploration on dermatology teaching by dermatopathology combined with "Learning Connect" platform - Wei WU; Yanxia CAI; Pingping MA; Lei CHEN; Fengjuan WANG; Shunting ZHOU; Yu ZHU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Dermatology, as a compulsory course for undergraduates in clinical medicine, is difficult for the beginner to master by traditional teaching mode due to the variety of diseases, pathogenesis and treatment methods. Starting from skin pathology and collaborating with the "Learning Connect" to carry out clinical medicine undergraduate teaching is a good reformed method of teaching for cultivating students' overall thinking. Typical pathological photos and descriptions of diseases are placed on "Learning Connect" platform prior to the class. Students can find the corresponding pathological descriptions of disease from the pathological photos during the preview, thereby predicting the nature, arrangement and distribution characteristics, pathogen, pathogenesis and treatment methods of the disease. Teachers and students interact in the classroom, using the dermatopathology as an introduction, integrating the pathogenesis, immunological mechanism, pathophysiology, clinical manifestations and treatment methods of the disease, comprehensively improving students' understanding and memory of the disease. At the end of course, teachers summarize and provide standard answers for definition, pathogenesis and treatment of disease, cultivating students' scientific logical thinking and independent knowledge acquisition ability. This article elaborates on the significance and the methods of combining skin pathology with the "Learning Connect" to carry out teaching of dermatology and sexually transmitted diseases, hopefully providing some reference for clinical educators.